Adenoids and clinical symptoms: Epidemiology of a cohort of 795 pediatric patients. Issue 12 (December 2015) - Pagella, Fabio; De Amici, Mara; Pusateri, Alessandro; Tinelli, Guido; Matti, Elina; Benazzo, Marco; Licari, Amelia; Nigrisoli, Sabrina; Quaglini, Silvana; Ciprandi, Giorgio; Marseglia, Gian Luigi
Abstract: Objective: Adenoid hypertrophy (AH) is very common in children and can cause airway obstruction. The aim of this retrospective study was to investigate the relationship between AH and other factors, including age, possible related symptoms, and allergies. Methods: Seven hundred and ninety-five patients (460 males, 335 females; mean age = 5.9 years; range age: 1–14 years) were seen in an ENT clinic for nasal symptoms. Nasal endoscopy was performed with a pediatric flexible endoscope. One hundred and sixty-nine patients had documented allergy sensitization. Patients were divided into two groups according to their age: group 1 included children aged 1–7 years, and group 2 included subjects aged 8–14 years. Results: Adenoid size was related to age ( p  < 0.0001). A logistic regression model – performed to evaluate adenoid grade considering, as dependent variables, age, sex, and the presence or absence of symptoms – was statistically significant ( p  < 0.001). Moreover, AH was more common ( p  = 0.0104) in patients with allergy sensitization, in particular in patients aged 8–14 years ( p  = 0.0043). Nasal obstruction (OR = 3.27) significantly predicted AH, whereas major age was not associated with pathological AH (OR = 0.81). Conclusions: The present retrospective study described the relationship between AH and other demographic and clinical factors. In conclusion, our findings demonstrated a significant association among pathological AH, age, and nasal obstruction.